2014
DOI: 10.1186/bf03351628
|View full text |Cite
|
Sign up to set email alerts
|

Stabilization of Venus’ climate by a chemical-albedo feedback

Abstract: It has been suggested that the atmospheric concentration of SO 2 observed on Venus coincides with the equilibrium concentration over pyrite-magnetite assemblage (pyrite-magnetite buffer). If the atmospheric SO 2 abundance is controlled by the chemical reaction at the planetary surface, we expect coupling between the atmospheric SO 2 abundance and the surface temperature. Here, we propose that the pyrite-magnetite buffer combined with cloud albedo feedback controls the surface temperature on Venus. We show that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 24 publications
0
9
0
Order By: Relevance
“…The high surface temperature of Venus enhances the importance of the gas‐solid reactions on the planetary surface in controlling the atmospheric composition, including infrared‐active species which control the greenhouse effect. Venus climate models that combine chemical reaction and radiative transfer in the atmosphere have demonstrated that such a coupling between surface chemical reactions and greenhouse effect will play an important role in controlling the surface environment [e.g., Hashimoto and Abe , 2000; Bullock and Grinspoon , 2001].…”
Section: Introductionmentioning
confidence: 99%
“…The high surface temperature of Venus enhances the importance of the gas‐solid reactions on the planetary surface in controlling the atmospheric composition, including infrared‐active species which control the greenhouse effect. Venus climate models that combine chemical reaction and radiative transfer in the atmosphere have demonstrated that such a coupling between surface chemical reactions and greenhouse effect will play an important role in controlling the surface environment [e.g., Hashimoto and Abe , 2000; Bullock and Grinspoon , 2001].…”
Section: Introductionmentioning
confidence: 99%
“…The climate and surface environment are also controlled by volcanism in that the associated degassing affects the atmospheric composition producing climate variations Grinspoon 1998, Hashimoto andAbe 2000). The dominant climate change is caused by changes in the H 2 SO 4 cloud cover above 48 km altitude, being induced by the increase in atmospheric sulfur produced by Venusian volcanos.…”
Section: Introductionmentioning
confidence: 98%
“…It has also been pro-posed that the atmospheric SO 2 mixing ratio is in equilibrium with a pyrite-magnetite assemblage. This chemical coupling would stabilize the climate through a cloud-albedo feedback (Hashimoto and Abe, 2000). Anomalous radar reflectivity areas observed at Venusian highlands might be attributed to pyrite produced by the atmosphere-surface interaction above, although heavy metal frost may also explain the reflectivity (Schaefer and Fegley, 2004).…”
Section: Surface Processesmentioning
confidence: 99%
“…Its climate and surface environment are also controlled by volcanism in that the associated degassing affects the atmospheric composition producing climate variations (Hashimoto and Abe, 2000). The current rate of volcanism, which is a key parameter determining the present chemical state of the atmosphere, is uncertain (Basilevsky et al, 1997).…”
Section: Surface Processesmentioning
confidence: 99%